2019
DOI: 10.1136/jech-2018-210709
|View full text |Cite
|
Sign up to set email alerts
|

Scope-of-practice laws and expanded health services: the case of underserved women and advanced cervical cancer diagnoses

Abstract: BackgroundUnderserved women (rural, minority or poor) are disproportionally diagnosed with late-stage cervical cancer, indicative of inadequate access to, and use of, preventative healthcare. The Institute of Medicine (IOM) has proposed that nurse practitioners (NP) can address provider shortages among underserved populations, but to reduce shortages, scope-of-practice laws that restrict the delivery of care, must be revised. We examined the IOM recommendation of NP expanded scope-of-practice laws on reducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Three other studies focused on health status of a specific care domain (Alexander & Schnell, 2019; Grecu & Spector, 2019; Smith-Gagen et al, 2019). The researchers reported significant improvement in self-reported mental health status and a decrease in mental health (Alexander & Schnell, 2019) and opioid-related mortality rates (Grecu & Spector, 2019) after expansion of NP prescriptive authority.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three other studies focused on health status of a specific care domain (Alexander & Schnell, 2019; Grecu & Spector, 2019; Smith-Gagen et al, 2019). The researchers reported significant improvement in self-reported mental health status and a decrease in mental health (Alexander & Schnell, 2019) and opioid-related mortality rates (Grecu & Spector, 2019) after expansion of NP prescriptive authority.…”
Section: Resultsmentioning
confidence: 99%
“…However, expanded access to care under FPA also can generate associated costs, especially for chronic conditions wherein medication use may be accessed or restored through care provided by NPs for underserved populations (Grant et al, 2017). Although initial costs of accessing care can increase short-term costs by instituting preventive measures (e.g., improved diabetes care), in the long term, health care costs actually could be reduced, through prevention of adverse consequences from poorly managed chronic conditions (Smith-Gagen et al, 2019; Spetz et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Giant meningiomas and frontoethmoidal encephaloceles, while certainly recognized throughout the world, are each relatively uncommon entities in their own right [1][2][3]11,12]. In underserved areas, both diagnostic and treatment delays may result in an increase in late-stage disease rates [6][7][8][9][10]. CSF leakage from long-silent encephaloceles is also a known phenomenon [12][13][14][15], but is usually preceded by polypectomy or biopsy of nasal mass [16].…”
Section: Discussionmentioning
confidence: 99%
“…Giant meningiomas (>5cm in diameter) are less common but may be more likely to be encountered in medically underserved areas due to lack of available resources for diagnosis or treatment, and a general trend of cultural mistrust of medical providers. Studies of racial, ethnic, and socioeconomic disparities within the United States found that minority populations and those in rural areas presented more often with advanced stages of tumor progression [6,7] or a later stage of disease in cancer cases [8][9][10].…”
Section: Introductionmentioning
confidence: 99%